Institute for Security, Defense and Peace at 40: Current Mission and Challenges Ahead - Spasov, Nikolco; Cvetkovski, Sergej; Pavleski, Aleksandar (Faculty of Security - Skopje, 2019)
Contemporary social changes and needs, inter alia initiate new challenges for the teaching process in higher education too. This year, the Institute for Security, Defense and Peace, is celebrating 40 years of its existence. In that context, the inevitable question arises about its past achievements as well as the current mission and new challenges. In addition, this paper analyzes the contemporary challenges for the institute, in the light of: 1) the need for certain changes to the curriculum of the Institute according to recent proposed amendments to the Law on Higher Education in Macedonia; 2) in particularly, adapting to the needs of the labor market; and 3) the need of promoted cooperation with other higher education institutions nationally and internationally. The analysis of those issues should enable creating an appropriate approaches framework that the Institute will have to take in the context of current and future educational and instructional challenges.
Keywords: Institute, Security, Defense and Peace, educational challenges, teaching challenges.